2000
DOI: 10.1103/physrevlett.84.1986
|View full text |Cite
|
Sign up to set email alerts
|

Double Quantum Dots as Detectors of High-Frequency Quantum Noise in Mesoscopic Conductors

Abstract: We propose a measurement setup for detecting quantum noise over a wide frequency range using inelastic transitions in a tunable two-level system as a detector. The frequency-resolving detector consists of a double quantum dot which is capacitively coupled to the leads of a nearby mesoscopic conductor. The inelastic current through the double quantum dot is calculated in response to equilibrium and nonequilibrium current fluctuations in the nearby conductor, including zero-point fluctuations at very low tempera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
382
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(390 citation statements)
references
References 14 publications
6
382
2
Order By: Relevance
“…Interactively coupled mesoscopic and nanoscale circuits, such as quantum wires (Debray et al, 2000(Debray et al, , 2001Laroche et al, 2011;Morimoto et al, 2003;Yamamoto et al, 2006), quantum dots (Aguado and Kouwenhoven, 2000;Onac et al, 2006) or point contacts (Khrapai et al, 2006(Khrapai et al, , 2007, provided new fruitful ways of studying Coulomb drag phenomena and revealed a plethora of interesting physics. These devices typically have dimensions smaller than the temperature length L T = v F /T and voltage-related length scale L V = v F /(eV ), and differ substantially from their two-dimensional quantumwell counterparts in several important ways.…”
Section: A Quantum Dots and Quantum Point Contactsmentioning
confidence: 99%
“…Interactively coupled mesoscopic and nanoscale circuits, such as quantum wires (Debray et al, 2000(Debray et al, , 2001Laroche et al, 2011;Morimoto et al, 2003;Yamamoto et al, 2006), quantum dots (Aguado and Kouwenhoven, 2000;Onac et al, 2006) or point contacts (Khrapai et al, 2006(Khrapai et al, , 2007, provided new fruitful ways of studying Coulomb drag phenomena and revealed a plethora of interesting physics. These devices typically have dimensions smaller than the temperature length L T = v F /T and voltage-related length scale L V = v F /(eV ), and differ substantially from their two-dimensional quantumwell counterparts in several important ways.…”
Section: A Quantum Dots and Quantum Point Contactsmentioning
confidence: 99%
“…25 It can also be traced to the "quantum" nature of the charge noise, i.e., a slight asymmetry between the charge noise at positive and negative frequencies. [32][33][34] As a result, the dynamics of the mode x becomes essentially classical, described by the Langevin equation, 14…”
Section: Modelmentioning
confidence: 99%
“…In Ref. 13, Aguado and Kouwenhoven considered the possibility of using a double quantum dot system as a detector of high-frequency noise. More recently, Josephson junctions were shown to be able to act as detectors of the third 14 and fourth moments of current fluctuations.…”
Section: Introductionmentioning
confidence: 99%